2018
DOI: 10.1186/s12978-018-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward sexual and reproductive health among adolescents and young people in urban and rural DR Congo

Abstract: BackgroundIn the Democratic Republic of Congo (DRC), onset of sexual intercourse is initiated during adolescence, however only two in ten sexually active unmarried women are using modern contraception. Improving adolescents’ and young peoples’ knowledge and practices related to sexual and reproductive health (SRH) is necessary to improve health outcomes. However, little is known about the SRH attitudes and needs among young people in the DRC. The study aims to contribute to the available evidence by examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 20 publications
7
48
0
1
Order By: Relevance
“…Adolescents should have access to a broad range of methods offered by qualified providers. Although adolescents often seek contraception outside of health facilities, the majority of our sample received their method in a public health facility, consistent with other findings in DRC in which some adolescents express a preference for going to a health facility over a pharmacy for contraception [24]. The use of a health facility is likely related to the high LARC use in this population (as LARCs are rarely available outside a health facility), similar to findings in a review of DHS data from adolescents in 33 countries [25].…”
Section: Plos Medicinesupporting
confidence: 89%
See 1 more Smart Citation
“…Adolescents should have access to a broad range of methods offered by qualified providers. Although adolescents often seek contraception outside of health facilities, the majority of our sample received their method in a public health facility, consistent with other findings in DRC in which some adolescents express a preference for going to a health facility over a pharmacy for contraception [24]. The use of a health facility is likely related to the high LARC use in this population (as LARCs are rarely available outside a health facility), similar to findings in a review of DHS data from adolescents in 33 countries [25].…”
Section: Plos Medicinesupporting
confidence: 89%
“…These findings are consistent with studies showing that adolescents often endorse social norms that reinforce gender inequalities, including a lack of control over their own SRH or lack of empowerment [29,30]. In addition, substantial stigma related to contraceptive use, including that women who use contraception are promiscuous, may contribute to this attitude [24,[31][32][33]. Research suggests that women's empowerment may be associated with modern contraceptive use [34,35].…”
Section: Plos Medicinesupporting
confidence: 86%
“…and STI services as well as dictating the type and nature of services young people should have.The review revealed that young people complained that discouraging and sometimes abusive remarks from health service providers were a great source of worry and a major barrier to them seeking SRH services in sub-Saharan Africa and across the world[37,[54][55][56][57][58].Negative attitude of health service providers was responsible for the embarrassment, fear and shame that the young people experienced which made it diffi cult for them to seek SRH services[36,[59][60][61][61][62][63]. Misconceptions about contraceptive methods such as, the use of hormonal methods like the pill and injectable cause infertility were found in the various studies to be major deterrent to some young women from seeking SRH services.…”
mentioning
confidence: 99%
“…The mean age of the participants studied by Duru et al [5] was 22.3±3.3 years and in a study by Opora et al [1] , the students were aged 10 -20 years, with a median age of 15 [1] . Attitudes about reproductive health among males and females aged 15-19 years were studied [15] . The study found 93% did not find sexuality education embarrassing.…”
Section: Resultsmentioning
confidence: 99%